DROSOPHILA S2 cell culture in a WAVE Bioreactor: potential for scaling up the production of the recombinant rabies virus glycoprotein - Decarli, Monize Caiado; Santos, Diogo Peres dos; Astray, Renato Mancini; Ventini-Monteiro, Daniella Cristina; Calil Jorge, Soraia Attie; Correia, Daniela Matilde; Silva, Juliana de Sa da; Rocca, Mayra Pereira [UNESP]; Langoni, Helio [UNESP]; Menozzi, Benedito Donizete [UNESP]; Pereira, Carlos Augusto; Torres Suazo, Claudio Alberto (Springer, 2018)
The transmembrane rabies virus glycoprotein (RVGP) is the main antigen of vaccine formulations used around the world to prevent rabies, the most lethal preventable infectious disease known. The objective of this work was to evaluate the potential of a bioreactor using wave-induced agitation in the initial steps of scaling up the rRVGP production process by a Drosophila melanogaster S2 cell line to produce rRVGP in sufficient quantities for immunization and characterization studies. Taking advantage of some remarkable features recognized in Drosophila S2 cells for scaling the culture process, a robust recombinant lineage (S2MtRVGPH-His) engineered by our group for the expression of rRVGP using a copper-inducible promoter was used in the bioreactor cultures. The WAVE Bioreactor was chosen because it represents an innovative approach to the cultivation of animal cells using single-use technology. For that purpose, we firstly established a procedure for culturing the S2MtRVGPH-His lineage in 100 mL Schott flasks. Using an inoculum of 5 x 10(5) cells/mL in culture medium (Sf900-III) induced with solution of CuSO4 (0.7 mM) and a convenient pH range (6.2-7.0), optimal parameter values such as time of induction (72 h) and temperature (28 degrees C) to increase rRVGP production could be defined. This procedure was reproduced in culture experiments conducted in a WAVE Bioreactor (TM) 2/10 using a 2 L Cellbag. The results in Schott flasks and inWAVE Bioreactor (TM) were very similar, yielding a maximum titer of rRVGP above of 1 mg.L-1. The immunization study showed that the rRVGP produced in the bioreactor was of high immunogenic quality.
Keywords: Rabies virus glycoprotein; Rabies vaccine; Drosophila melanogaster S2; WAVE Bioreactor; Scale-up; Recombinant protein production